Julo-Julo as Social Capital: Strengthening the Economic Resilience of Traders at Sangkumpal Bonang Market, North Sumatra - Replita, Replita; Effendi, Nusyirwan; Ophyandri, Taufika; Miko, Alfan (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The global economic crisis caused by many factors continues to impact the global world, including Indonesia. Conventional traders have used Julo-julo as a form of social capital to strengthen tradition-based economic practices amidst the pressures of the global free market. However, this phenomenon remains underexplored in the existing academic literature. In addition to addressing gaps in previous research, this study specifically examines how the traditional economic system that uses julo-julo by conventional traders in Sangkumpal Bonang Market, North Sumatra. Using a qualitative descriptive approach rooted in the case study method, analyzed with social capital theory. Data are based on three types, namely, observation, in-depth interviews and literature studies. Interviews were conducted with traders in Sangkumpal Bonang Market, while the literature analyzed were journal articles, proceedings, books related to the discussion. This study concludes that there are three dimensions that are key to the significant contribution of julo-julo, namely; First, this system is based on a social network built on trust, emotional closeness, and shared norms. Second, Julo-Julo offers high accessibility and practical flexibility while encouraging financial discipline among its members. Third, this system enhances the capacity of traders to manage capital, grow their businesses, and remain resilient under economic pressure. This study offers meaningful insights into the development of a tradition-based, community-rooted economic model as a viable strategy to address the challenges posed by global market liberalization.